Clinical And Transfusiological Assessment Of Prp-Therapy In The Treatment Of Men's Infertility In Non-Structural Azoospermia (Texas Journal of Medical Science, 2026)
Non-obstructive azoospermia (NOA) is one of the most complex forms of male infertility, caused by a primary disruption of spermatogenesis. The purpose of this study was the clinical and transfusiological assessment of the effectiveness and safety of PRP-therapy in patients with non-obstructive azoospermia. The study included 60 patients with confirmed NA, who underwent autologous PRP intrastiticular administration. Clinical, hormonal, ultrasound, and laboratory indicators were assessed before treatment and 3 and 6 months after treatment